A multidisciplinary approach to understanding skeletal dysplasias. Issue 5 (September 2011) - Kinning, Esther; McDevitt, Helen; Duncan, Rod; Ahmed, S Faisal
The skeletal dysplasias are a heterogeneous group of conditions of abnormal cartilage and bone development, resulting in a wide range of phenotypes of variable severity from perinatal lethality to mild short stature. Elucidation of the molecular mechanisms underlying these disorders is allowing us to understand more about the etiology of these conditions and classify them based upon the underlying gene defect. This article will discuss the development of bone and cartilage in relation to these conditions, present a clinical approach to their diagnosis and management, and consider new avenues of therapy.